The Emerging Role of Insulin and Insulin-Like Growth Factor Signaling in Cancer Stem Cells - Malaguarnera, Roberta; Belfiore, Antonino (Frontiers in Endocrinology, 2014)
Cancer cells frequently exploit the IGF signaling, a fundamental pathway mediating development, cell growth and survival. As a consequence, several components of the IGF signaling are deregulated in cancer and sustain cancer progression. However, specific targeting of IGF-IR in humans has resulted efficacious only in small subsets of cancers, making researches wondering whether IGF system targeting is still worth pursuing in the clinical setting. Although no definite answer is yet available, it has become increasingly clear that other components of the IGF signaling pathway, such as IR-A, may substitute for the lack of IGF-IR, and induce cancer resistance and/or clonal selection. Moreover, accumulating evidence now indicates that IGF signaling is a central player in the induction/maintenance of epithelial mesenchymal transition (EMT) and cell stemness, two strictly related programs, which play a key role in metastatic spread and resistance to cancer treatments. Here we review the evidences indicating that IGF signaling enhances the expression of transcription factors implicated in the EMT program and has extensive crosstalk with specific pathways involved in cell pluripotency and stemness maintenance. In turn, EMT and cell stemness activate positive feed-back mechanisms causing upregulation of various IGF signaling components. These findings may have novel translational implications.